The Influence of Shotloc Training on Accuracy Shooting Free Throw Women’s Basketball Singaperbangsa University Karawang - Rafiqa Adawiyyah; Qorry Armen Gemael; R. Retna Kinati Dewi (UNIVERSITAS NEGERI MAKASSAR, 2023)
This research is difficult to positionreturnorgrippingpalmlack of handsconsistencyin a releaseshe wasmomentshooting,causeclearanceWhichlesswell in one game. As a result of the grip on holding the ball wrong then it causes when doing it shooting free throw accuracy is not right on the basketball hoop, therefore researchers provide toolsshotloc. The purpose of this research is to improve accuracy in shooting free throws. This type of research is experimental with a quantitative approach and research design in fact-group comparison. The population is 83 athletes and the sample is 40 female athletes with technique purposive sampling. This research instrument uses a free-throw test. Data analysis used t-test analysis and previously tested for normality and homogeneity. The pretest data has an average of 23.35 and the post-test has an average of 11.58. The normality test using the Shapiro-Wilk pretest results has a significant 0.121 > 0.05, so the pretest data is normally distributed, and the normality test using the Shapiro-Wilk on the posttest results has a significant 0.089 > 0.05, so the posttest data is normally distributed. The homogeneity test has a Sig value. 0.405 > 0.05, it can be obtained that the data distribution is homogeneous. Then the Paired t-test shows that the value of Sig. (2-tailed) of 0.000 <0.05, it can be concluded that there is a significant difference between the results usingshotloc on the Pretest and Posttest data.